Attack and counterattack efficiency in elite male volleyball - Klaricic, I.; Grgantov, Z.; Milic, M. (World Congress of Performance Analysis of Sport XII, 2018)
Forty randomly selected volleyball sets played in the European League for Men in years 2011. and 2012. were analyzed in order to determine the differences between the efficiency of the attack phase spike and the counter-attack phase spike. Reliability analysis conducted on a sample of 6 randomly selected sets determined a high intra-rater and inter-rater reliability (R = 0.951 and 0.923 respectively). The T-test for independent samples did not determine any significant differences between the efficiency of the attack phase spike and the counter-attack phase spike. The Mann Whitney U test determined significant differences in the efficiency of the counter-attack phase spike between winning and losing teams but not in the efficiency of the attack phase spike. The obtained results indicate that considerable attention has to be devoted to the improvement of the team`s play in the counter-attack phase play in the training process.